Methyl 2-{4-chloro-2-[5-chloro-2-(2-methoxy-2-oxoethoxy)benzyl]phenoxy}acetate - Michaela Pojarová; Michal Dušek; Zdeňka Sedláková; Emanuel Makrlík (Acta Crystallographica Section E, 2012)
In the crystal structure of the title compound, C19H18Cl2O6, molecules are connected via weak C—H...π interactions into closely packed dimers.